Geopolymer material prepared from solid caustic soda red mud and method

By mixing the calcined red mud with other materials and grinding them to prepare the dipoly polymer material, the problems of high hardness and high radioactivity index of the red mud powder are solved, and the high activity index and low radioactivity index of the dipoly polymer material are achieved, thereby improving the Its application safety in the field of building materials.

CN119390373APending Publication Date: 2025-02-07GUIZHOU BUILDING MATERIALS RES & DESIGN INST CO LTD

Patent Information

Application Number
CN202411658869.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Red mud is prone to agglomeration when grinding alone, resulting in poor grinding effect. Its high radioactivity index does not meet the safety standards in the field of building materials, affecting its resource utilization.

Method used

After calcining the red mud in a rotary kiln, it is mixed with materials such as phosphogypsum, coal-fired furnace slag, coal gangue and exciter, and prepares the glycopolymer material by grinding, controlling the mass ratio of each raw material and the preparation of the exciter. Stimulate the overall activity of the constituent system.

Benefits of technology

The activity index of the geopolymer material is improved to reach more than 95%, while the internal and external irradiation index is reduced, agglomeration phenomenon is avoided, and the fluidity and application safety of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390373A_ABST
    Figure CN119390373A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste resource utilization, in particular to a geopolymer material prepared by using red mud as a raw material and a method, the red mud is calcined and then added with ardealite, coal-fired slag, coal gangue and the like to construct a geopolymer material composition system, and the geopolymer material is prepared by adding an exciting agent and grinding. According to the geopolymer material disclosed by the invention, the overall activity of the composition system is excited by adding the phosphogypsum, the coal gangue, the solid alkali red mud and the exciting agent, and the dosage control of the coal-fired slag, the phosphogypsum, the coal gangue, the solid alkali red mud and the exciting agent is combined, so that the activity index (28d) of the geopolymer material reaches 95% or above, the internal illumination index is reduced to 0.6 or below, the external illumination index is reduced to 0.8 or below, and the application safety of the geopolymer material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste resource utilization, and in particular to a geopolymer material and a method for preparing the geopolymer material by using solid alkali red mud. Background Art

[0002] Red mud is an industrial solid waste generated when preparing alumina from bauxite using the Bayer process, sintering process or combined process. Generally, about 1.5 tons of red mud are discharged for every ton of alumina produced. As the output of alumina gradually increases, the amount of red mud discharged also increases, resulting in a large amount of red mud solid waste maintaining a high stockpile volume for a long time. Therefore, the resource utilization of red mud has received widespread attention from technicians in this field.

[0003] Geopolymer material is an aluminum silicate gel material composed of a three-dimensional gel network structure of SiO4 and AlO4 tetrahedrons. It has good mechanical properties, high temperature resistance, acid resistance, high specific surface area and high porosity, etc., which makes it widely used in the field of building materials. For example: Patent No. 201910950345.6 discloses that its raw materials fly ash and active industrial solid waste (blast furnace slag, steel slag and / or red mud) are activated by alkali (alkaline activator: water glass) to prepare geopolymer material, and then crush and screen it as coarse aggregate. For another example: Patent application No. 202010520411.9 discloses that industrial solid waste (fly ash, steel slag and / or red mud) is dried and ground into powder particles, and then fully mixed with inorganic gel materials, reflective materials, wear-resistant fillers, etc., and prepared into road marking paint based on geopolymer material under the activation of sodium hydroxide, sodium sulfate, sodium carbonate, potassium hydroxide and / or potassium sulfate as activators. Another example: Patent No. 202310037457.9 discloses a material prepared from amorphous aluminosilicate and an alkali activator, wherein the amorphous aluminosilicate includes at least one raw material selected from composite fly ash, slag, phosphorus slag, steel slag, nickel slag, ferromanganese slag, coal gangue, and lithium slag; the composite fly ash includes a first fly ash and calcium-containing solid waste; the calcium-containing solid waste includes at least one of a second fly ash, slag, and red mud; the alkali activator includes at least one of alkali metal hydroxides, alkali metal silicates, alkali metal aluminates, and alkaline earth metal silicates to prepare alkali-activated geopolymer materials for use in building materials.

[0004] It can be seen that there are already a large number of technical solutions in the prior art for using red mud as a raw material to prepare geopolymer materials, and the prepared geopolymer materials are widely used in the field of building materials, realizing the resource utilization of red mud in the field of geopolymer materials. However, the main components of red mud are CaCO3, Fe2O3, (Mg,Al)6(Si,Al)4O 10 (OH)8, (Mg,Fe)6(Si,Al)4O 10 (OH)8 and Mg3Mn2Si3AlO10 (OH) 10 Salts mainly containing Si and Al, etc., are very likely to agglomerate if ground separately, resulting in poor grinding effect and poor performance of the prepared geopolymer material. At the same time, red mud is an industrial solid waste, and its internal and external radiation index is relatively high, usually greater than 1.5, which does not meet the national standard of less than 1, resulting in the addition of red mud in the field of building materials should not be too high, which in turn affects the disposal of the red mud stockpile. Summary of the invention

[0005] Based on the above technical problems, the present invention provides a geopolymer material and method prepared by using solid alkali red mud. Nitrogen-fixing red mud is used as the main raw material of the geopolymer material. In combination with the addition of materials such as phosphogypsum, coal-fired slag, coal gangue, and activators, the activity index of the geopolymer material is not only improved, so that the activity index (28d) is greater than 95%, but also the internal irradiation index of the geopolymer material prepared with red mud as the main raw material is ≤0.6, and the external irradiation index is ≤0.8. At the same time, the difficulty of the red mud grinding process is reduced, the agglomeration phenomenon in the red mud grinding process is avoided, the difficulty of preparing the geopolymer material by grinding with red mud as the raw material is reduced, and the fluidity of the geopolymer material is enhanced.

[0006] The specific technical solution is:

[0007] One of the purposes of the present invention is to provide a method for preparing geopolymer material using solid alkali red mud, comprising: taking coal-fired furnace slag, coal gangue, phosphogypsum, an activator and solid alkali red mud to mix into a mixture, and then grinding the mixture to a specific surface area of ​​≥480 m2 / kg to obtain a geopolymer material; wherein the sum of the mass of the phosphogypsum and the activator is 10% of the mass of the mixture, and the amount of the activator is ≥ the amount of the phosphogypsum; the coal-fired furnace slag accounts for ≥10% of the mass of the mixture, the coal gangue accounts for ≥20% of the mass of the mixture, the remainder is solid alkali red mud, and the mass ratio of the solid alkali red mud to the coal-fired furnace slag is <6:1; the solid alkali red mud is obtained by calcining red mud in a rotary kiln.

[0008] By calcining red mud in a rotary kiln, the solid alkali inhibition effect is achieved, so that the alkali content in the red mud is solidified and not easy to precipitate, and coal-fired slag, coal gangue, phosphogypsum and solid alkali red mud are added to construct a geopolymer material composition system. The activator is introduced and the overall activity of the composition system is stimulated through grinding, so that the geopolymer material can meet the performance requirements of the composite admixture, enhance the activity of the geopolymer material, reduce the radioactivity index, and improve the safety of resource utilization of solid waste such as red mud.

[0009] In order to ensure that the overall 28d activity index of the geopolymer material reaches more than 95% and the radioactivity index is reduced, preferably, the mass ratio of the solid alkali red mud to the coal-fired furnace slag is (4.8-11): 3. More preferably, the mass ratio of the solid alkali red mud to the coal-fired furnace slag is 4.8:1.

[0010] In order to ensure the activation effect of the activator on the geopolymer material composition system, improve the 28d activity index of the geopolymer material, reduce the internal and external illumination indexes, and then improve the safety of red mud application, preferably, the activator is a mixture of potassium hydroxide, sodium silicate, cement, and polycarboxylate water reducer, the mass of the potassium hydroxide is equal to that of the sodium silicate, the mass of the cement is equal to that of the polycarboxylate water reducer, and the mass ratio of the potassium hydroxide to the cement is (1-2):(3-4). More preferably, the mass ratio of the potassium hydroxide to the cement is 1:4 or 3:7 or 2:3.

[0011] The cement created by the present invention includes but is not limited to P·O32.5 or P·O42.5. For example, P·O52.5, P·C32.5, CA-50, etc. can also be used.

[0012] The coal gangue created by the present invention is solid waste discharged from the coal mining process or solid waste discharged from the coal washing process.

[0013] In order to enhance the solid alkali inhibition effect of red mud and ensure that the activity index of the geopolymer material reaches more than 95%, preferably, the calcination is carried out at a temperature of 1000-1200°C for 30-60 minutes. More preferably, the calcination is carried out at a temperature of 1100°C for 45 minutes.

[0014] The second purpose of the invention is to provide a geopolymer material prepared by the above method, whose 28d activity index reaches more than 95%, and the internal illumination index is ≤0.6, and the external illumination index is ≤0.8, which greatly improves the application safety of the geopolymer material prepared by using red mud as raw material.

[0015] Compared with the prior art, the technical effects created by the present invention are embodied in:

[0016] The calcined red mud is mixed with phosphogypsum, coal slag, coal gangue, etc. to form a geopolymer material composition system, and the geopolymer material is prepared by adding an activator and grinding, so that the overall activity of the composition system is stimulated, and the amount of coal slag, phosphogypsum, coal gangue, solid alkali red mud and activator is controlled, so that the activity index (28d) of the geopolymer material reaches more than 95%, and at the same time the internal illumination index is reduced to below 0.6, and the external illumination index is reduced to below 0.8, thereby enhancing the safety of the application of the geopolymer material.

[0017] The invention has the advantages of simple preparation process, low preparation cost, strict control of the addition amount of each raw material component, and combined with the selection and preparation of the stimulator raw material component, the active stimulation effect is improved, the difficulty of grinding is reduced, and the agglomeration phenomenon caused by grinding various raw materials separately is avoided, the fluidity of the geopolymer material is improved, the quality of the geopolymer material is guaranteed, and the preparation cycle of the geopolymer material is shortened.

[0018] The red mud used in the invention can be red mud produced by the sintering process, the combined process or the Bayer process to produce alumina, which can reduce the difficulty of red mud treatment and increase the added value of red mud utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to facilitate those skilled in the art to fully understand the technical solution of the present invention, the following description is made on the provided drawings in combination with the content of the technical solution and the provided drawings.

[0020] Figure 1 Create a process flow chart for the present invention. DETAILED DESCRIPTION

[0021] In order to facilitate those skilled in the art to correctly understand the present invention and enable them to fully understand the technical content of the present invention, the technical solution of the present invention is further explained below in combination with specific implementation methods and drawings, but this explanation does not limit the scope of protection required for the present invention.

[0022] like Figure 1 As shown, in certain embodiments, a method for preparing a geopolymer material using nitrogen-fixing red mud comprises:

[0023] (1) The red mud is calcined in a rotary kiln at 1000-1200°C for 30-60 min, for example, calcined at 1000°C for 60 min, calcined at 1050°C for 60 min, calcined at 1100°C for 45 min, calcined at 1150°C for 45 min, calcined at 1200°C for 30 min, calcined at 1200°C for 40 min, calcined at 1200°C for 50 min, etc., to obtain solid alkali red mud; by calcining at this temperature for a corresponding time, the alkali content in the red mud can be greatly promoted to be solidified or reduced, the solid alkali inhibition effect of the red mud can be achieved, the alkali precipitation rate of the red mud in the preparation process of the geopolymer material can be reduced, the overall performance of the geopolymer can be guaranteed, and it is helpful to improve the activity index (28d) of the geopolymer material; at the same time, when calcining at 1200°C, it is not suitable to calcine for 60 min.

[0024] (2) Mix coal-fired furnace slag, coal gangue, phosphogypsum, activator and solid alkali red mud into a mixture, and then grind the mixture to a specific surface area ≥ 480 m2 / kg, for example: 480 m2 / kg, 500 m2 / kg, 550 m2 / kg, 600 m2 / kg, or 650 m2 / kg, etc.; Grinding the mixture of coal-fired furnace slag, coal gangue, phosphogypsum, activator and solid alkali red mud greatly improves the phenomenon that red mud is easily agglomerated when ground alone, reduces the difficulty of grinding red mud, and helps to improve the overall performance of geopolymer materials.

[0025] Among them, the sum of the mass of phosphogypsum and the activator is 10% of the mass of the mixture, the mass of coal-fired slag accounts for ≥10% of the mass of the mixture, for example, the mass of coal-fired slag accounts for 10-25% of the mass of the mixture (10%, 11%, 13%, 14%, 15%, 17%, 19%, 20%, 21%, 22%, 23%, 24% or 25%), the mass of coal gangue accounts for ≥20% of the mass of the mixture, for example, the mass of coal gangue accounts for 20-25% of the mass of the mixture (20%, 21%, 22%, 23%, 24% or 25%), the remainder is solid alkali red mud, and the mass ratio of the solid alkali red mud to the coal-fired slag is <6:1, and the mass of the activator is ≥the mass of the phosphogypsum. Properly controlling the dosage of solid alkali red mud, coal-fired slag, coal gangue, phosphogypsum and activator can improve the comprehensive performance of the geopolymer material prepared by grinding, ensure that the red mud can be consumed at the maximum amount, enhance the fluidity of the geopolymer material, improve the activity index (28d), reduce the internal and external radiation index, and improve the application safety of the geopolymer material prepared with red mud as raw material.

[0026] In some embodiments, the mass ratio of the solid alkali red mud to the coal-fired furnace slag is (4.8-11):3, for example: 1.6:1, 4.9:3, 5:3, 2:1, 7:3, 7.5:3, 8:3, 3:1, 10:3, 11:3, etc. The activity index (28d) can reach more than 95%, and the internal illumination index is ≤0.6, and the external illumination index is ≤0.8.

[0027] In some embodiments, the activator is a mixture of potassium hydroxide, sodium silicate, cement, and polycarboxylate water reducer, wherein the mass of the potassium hydroxide is equal to that of the sodium silicate, the mass of the cement is equal to that of the polycarboxylate water reducer, and the mass ratio of the potassium hydroxide to the cement is (1-2):(3-4), for example: 1:4, 1:2, 1:3, 2:3, 2:7, 3:7, 4:7, etc. This helps to improve the overall performance of the geopolymer material.

[0028] In the invention, the cement includes but is not limited to P·O32.5 or P·O42.5. In addition, in some embodiments, P·O52.5, P·C32.5, CA-50 and other cements can also be used.

[0029] In order to better verify the technical effects that can be brought about by the present invention, the researchers of the present invention carried out the following laboratory sample preparation and detection research.

[0030] The red mud used in the present invention comes from an aluminum oxide production enterprise in Guizhou. Its main components are: Al2O3 20.34%, Fe2O3 27.31%, SiO2 24.6%, Na2O 7.3%; its internal irradiation index (I Ra ) is 2.03, and the external radiation index (I r ) is 3.24.

[0031] The coal gangue used in the present invention is solid waste discharged by a coal mining enterprise in Guizhou. Its main components are: SiO2 53.11%, Al2O3 17.43%, Fe2O3 4.16%, CaO 1.32%, MgO 1.17%; its internal irradiation index (I Ra ) is 0.7, and the external radiation index (I r ) is 0.8.

[0032] The phosphogypsum used in the present invention is industrial solid waste produced by a phosphorus chemical enterprise in Guizhou, and the solid waste is obtained by drying it to a constant weight. The main component is CaSO4, with a content of 87.32%, and its internal radiation index (I Ra ) is 0.6, and the external radiation index (I r ) is 0.9.

[0033] The coal-fired slag used in the present invention is from the slag discharged from a coal-fired power plant in Guizhou. The main components are SiO242.15%, Al2O333.41%, Fe2O35.7%, CaO3.2%, and its internal irradiation index (I Ra ) is 0.6, and the external radiation index (I r ) is 0.7.

[0034] Experiment 1: Study on the influence of raw material ratio on geopolymer material performance

[0035] The red mud was calcined at 1000℃ for 55min to obtain solid alkali red mud; 10kg of potassium hydroxide, 10kg of sodium silicate, 40kg of P·O42.5 cement, and 40kg of polycarboxylic acid water reducer were mixed to prepare an activator. The solid alkali red mud, coal gangue, coal-fired slag, phosphogypsum, and activator were mixed into a mixture according to the proportion group described in Table 1 below, and ground by a pulverizer to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material; the fineness (45μm sieve residue), fluidity ratio, 28d activity index, mortar compressive strength ratio, boiling method stability qualification, and radioactivity of the geopolymer material were tested, and the results were recorded in Table 1 (tested in accordance with JG / T486-2015 "Composite admixtures for concrete", and each group of data was tested three times to take the average value).

[0036] Table 1

[0037]

[0038]

[0039] It can be seen from Table 1 that by properly controlling the ratio of solid alkali red mud, phosphogypsum, coal gangue, coal-fired slag, and activator, it is helpful to make the 28d activity index of the geopolymer material reach more than 95%, and the internal irradiation index of the obtained geopolymer material is ≤0.6, and the external irradiation index is ≤0.8. When the mass ratio of solid alkali red mud to coal-fired slag is ≥6:1 or the amount of phosphogypsum> the amount of activator or the amount of coal gangue is <20%, the 28d activity index of the obtained geopolymer material will be lower than 90%, and the internal irradiation index of the obtained geopolymer material will be ≥0.8, and the external irradiation index will be ≥1.1. It can be seen that the invention will help to improve the 28d activity index of the geopolymer material and enhance the safety of the use of geopolymer materials in the field of building materials through proper control of the mutual content of solid alkali red mud, phosphogypsum, coal gangue, coal-fired slag, and activator.

[0040] Experiment 2: Study on the influence of red mud calcination temperature and time on the performance of geopolymer materials

[0041] During the calcination of solid alkali red mud, the red mud was calcined at the calcination time and calcination temperature shown in Table 2, and the solid alkali red mud obtained by calcination at different calcination times and different calcination temperatures was mixed with coal gangue, coal-fired slag, phosphogypsum, and activator according to the ratio 3 in Test 1 to form a mixture, and the mixture was ground by a pulverizer to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material. According to Test 1, the fineness (45μm sieve residue), fluidity ratio, 28d activity index, mortar compressive strength ratio, boiling method stability qualification, and radioactivity of the geopolymer material were tested, and the results were recorded in Table 2 (tested according to JG / T486-2015 "Compound Admixtures for Concrete", and each group of data was tested three times and the average value was taken).

[0042] Table 2

[0043]

[0044]

[0045] It can be seen from Table 2 that the red mud calcination temperature and calcination time should vary within an appropriate range. If the calcination temperature is too high and the calcination time is too short or too long, the 28d activity index of the geopolymer material will be affected, resulting in poor comprehensive performance of the geopolymer material prepared with red mud as raw material.

[0046] Experiment 3: Study on the influence of changes in activator composition on the performance of geopolymer materials

[0047] Potassium hydroxide, sodium silicate, cement, and polycarboxylic acid water reducer are mixed in the proportions shown in Table 3 below to prepare an activator, and the activator, solid alkali red mud, coal gangue, coal-fired slag, and phosphogypsum are mixed into a mixture according to the proportion 1 in Test 1, and the mixture is ground by a pulverizer to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material. According to Test 1, the fineness (45μm sieve residue), fluidity ratio, 28d activity index, mortar compressive strength ratio, boiling method stability qualification, and radioactivity of the geopolymer material are tested, and the results are recorded in Table 3 (tested in accordance with JG / T 486-2015 "Composite admixtures for concrete", each group of data is tested three times and the average value is taken).

[0048] Table 3

[0049]

[0050] It can be seen from Table 3 that when the mass contents of cement and polycarboxylate water-reducing agent in the activator are equal, the mass contents of potassium hydroxide and sodium silicate are equal, and the mass ratio of potassium hydroxide to cement is (1-2): (3-4), the 28d activity index of the geopolymer material can be enhanced, and the internal radiation index and external radiation index can be reduced, thereby improving the application safety of geopolymer materials prepared with red mud as raw material in the field of building materials.

[0051] The technical solution created by this invention has been provided to building materials manufacturers for pilot production research. The specific research contents are as follows:

[0052] Example 1

[0053] The red mud produced by the Bayer process for producing alumina is calcined in a rotary kiln at 1000°C for 60 minutes to obtain solid alkali red mud; 10kg of potassium hydroxide, 10kg of sodium silicate, 40kg of cement (P·O42.5), and 40kg of polycarboxylic acid water reducer are mixed to prepare an activator; 40kg of solid alkali red mud, 25kg of coal-fired slag, 25kg of coal gangue, 5kg of phosphogypsum, and 5kg of activator are mixed to form a mixture, and the mixture is ground to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material.

[0054] Example 2

[0055] The red mud produced by the Bayer process for producing alumina is calcined in a rotary kiln at 1100°C for 45 minutes to obtain solid alkali red mud; 15kg of potassium hydroxide, 15kg of sodium silicate, 35kg of cement (P·O42.5), and 35kg of polycarboxylic acid water reducer are mixed to prepare an activator; 50kg of solid alkali red mud, 20kg of coal-fired slag, 20kg of coal gangue, 5kg of phosphogypsum, and 5kg of activator are mixed to form a mixture, and the mixture is ground to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material.

[0056] Example 3

[0057] The red mud produced by the Bayer process of producing alumina is calcined in a rotary kiln at 1200°C for 30 minutes to obtain solid alkali red mud; 20kg of potassium hydroxide, 20kg of sodium silicate, 30kg of cement (P·O42.5) and 30kg of polycarboxylic acid water reducer are mixed to prepare an activator; 55kg of solid alkali red mud, 15kg of coal-fired slag, 20kg of coal gangue, 3kg of phosphogypsum and 7kg of activator are mixed to form a mixture, and the mixture is ground to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material.

[0058] Example 4

[0059] The red mud produced by the Bayer process for producing alumina is calcined in a rotary kiln at 1200°C for 60 minutes to obtain solid alkali red mud; 15kg of potassium hydroxide, 15kg of sodium silicate, 40kg of cement (P·O42.5) and 30kg of polycarboxylic acid water reducer are mixed to prepare an activator; 60kg of solid alkali red mud, 10kg of coal-fired slag, 20kg of coal gangue, 3kg of phosphogypsum and 7kg of activator are mixed to form a mixture, and the mixture is ground to a specific surface area of ​​≥480㎡ / kg to obtain a geopolymer material.

[0060] The geopolymer materials obtained from the pilot production of Examples 1-4 were tested for fineness (45 μm sieve residue), fluidity ratio, 28d activity index, mortar compressive strength ratio, water content, chloride ion content, sulfur trioxide content, boiling method stability qualification, and radioactivity according to JG / T 486-2015 "Composite admixtures for concrete". Each group of data was tested three times and the average value was taken. The results are recorded as shown in Table 4 below:

[0061] Table 4

[0062]

[0063] The invention prepares solid alkali red mud by properly controlling the calcination time and temperature of the red mud rotary kiln, combines the solid alkali red mud, coal-fired furnace slag, coal gangue, phosphogypsum and an activator in an appropriate mass ratio, and then grinds the mixture to prepare the geopolymer material, thereby simplifying the preparation process of the geopolymer material and reducing the probability of agglomeration in the red mud grinding process, reducing the grinding difficulty, ensuring the excellent comprehensive performance of the geopolymer material, making the 28d activity index of the geopolymer material reach more than 95%, and compared with the raw materials used in the geopolymer material, reducing the radioactivity, making the internal irradiation index of the geopolymer material ≤0.6, and the external irradiation index ≤0.8, thereby improving the safety of the application of the geopolymer material in the field of building materials.

[0064] In addition, the invention also properly controls the raw materials in the activator preparation process to ensure that the activator enhances the activity of the solid alkali red mud-coal gangue-coal slag-phosphogypsum overall system when preparing geopolymer materials by activating a mixture of industrial solid wastes such as red mud, coal gangue, coal-fired furnace slag, and phosphogypsum, so that the 28d activity index of the geopolymer material reaches more than 95%; at the same time, the solid alkali alkali inhibition effect is improved, so that the radioactivity index in the prepared geopolymer material is greatly reduced compared with the raw materials, thereby improving the safety of the application of industrial solid wastes such as red mud, coal gangue, coal-fired furnace slag, and phosphogypsum in the field of building materials. In addition, the present invention conducted a 7d activity index test on the geopolymer materials prepared in Examples 1 to 4, and the results were as follows: the 7d activity index of the geopolymer materials obtained in Examples 1 to 3 all reached more than 80%, while the 7d activity index of the geopolymer material obtained in Example 4 was only 60%; it can be seen that in the preparation of geopolymer materials using red mud as raw material, the mixing ratio of solid alkali red mud, coal gangue, coal-fired slag, phosphogypsum and activator, as well as the ratio of each raw material component in the activator will have a greater impact on the 7d activity index of the geopolymer material.

[0065] The invention also combines grinding with raw material proportioning, so that the raw material mixing and grinding processes are mutually modified, thereby avoiding the agglomeration of solid alkali red mud during the grinding process, improving the grinding effect, and making the fluidity ratio of the geopolymer material reach more than 105, thereby improving the fluidity of the geopolymer material.

[0066] The invention has a simple process flow and is easy to operate, which helps to shorten the geopolymer material preparation cycle and reduce the geopolymer material preparation cost.

[0067] Other matters not covered by the present invention may be achieved by conventional technical means with reference to the prior art or common knowledge known to those skilled in the art, for example, drying phosphogypsum to constant weight.

Claims

1. A method for preparing geopolymer material using solid alkali red mud, characterized in that: include: Coal-fired furnace slag, coal gangue, phosphogypsum, an activator and solid alkali red mud are mixed into a mixture, and the mixture is then ground to a specific surface area of ​​≥480 m2 / kg to obtain a geopolymer material; wherein the sum of the mass of the phosphogypsum and the activator is 10% of the mass of the mixture, and the amount of the activator is ≥ the amount of the phosphogypsum; the coal-fired furnace slag accounts for ≥10% of the mass of the mixture, the coal gangue accounts for ≥20% of the mass of the mixture, and the remainder is solid alkali red mud, and the mass ratio of the solid alkali red mud to the coal-fired furnace slag is <6:1; the solid alkali red mud is obtained by calcining red mud in a rotary kiln.

2. The method for preparing geopolymer material using solid alkali red mud according to claim 1, characterized in that: The mass ratio of the solid alkali red mud to the coal-fired furnace slag is (4.8-11):

3.

3. The method for preparing geopolymer material using solid alkali red mud according to claim 1 or 2, characterized in that: The mass ratio of the solid alkali red mud to the coal-fired furnace slag is 4.8:

1.

4. The method for preparing geopolymer material using solid alkali red mud according to claim 1, characterized in that: The activator is prepared by mixing potassium hydroxide, sodium silicate, cement and polycarboxylate water reducer. The mass of the potassium hydroxide is equal to that of the sodium silicate, the mass of the cement is equal to that of the polycarboxylate water reducer, and the mass ratio of the potassium hydroxide to the cement is (1-2):(3-4).

5. The method for preparing geopolymer material using solid alkali red mud as claimed in claim 4, characterized in that: The mass ratio of the potassium hydroxide to the cement is 1:4 or 3:7 or 2:

3.

6. The method for preparing geopolymer material using solid alkali red mud as claimed in claim 4, characterized in that: The cement is P·O32.5 or P·O42.

5.

7. The method for preparing geopolymer material using solid alkali red mud according to claim 1, characterized in that: The coal gangue is solid waste discharged during the coal mining process.

8. The method for preparing geopolymer material using solid alkali red mud according to claim 1, characterized in that: The calcination is carried out at a temperature of 1000-1200° C. for 30-60 minutes.

9. The method for preparing geopolymer material using solid alkali red mud according to claim 1, characterized in that: The calcination was carried out at a temperature of 1100° C. for 45 minutes.

10. Geopolymer material prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of high-volume fly ash-based water permeable brick

    CN110606720A

  • Geopolymer material-based road marking coating and preparation method thereof

    CN111635652A

  • Alkali-activated geopolymer materials and their applications

    CN115974431B

Cited By

  • Roadbed material prepared based on coal gangue material and method

    CN122426988A